User Experience Otomatisasi Pajak Sebagai Rule Base Impact COVID-19 - Andrianingsih, Andrianingsih; Suparman, Kodim; Maharani, Anggita Putri (Forum Kerjasama Pendidikan Tinggi, 2022)
The Covid-19 pandemic in 2021 is very influential. It has a significant impact on various elements, ranging from the business sector to the worker sector, where the pandemic can destroy the entire sector indiscriminately. It is just that there is one industrial sector that can survive the Covid-19 pandemic attack, namely the industrial sector based on information technology or digital business. Departing from the industry sector that can survive, then pajakonline.com try their luck by starting to design their business into the realm of information technology or digital. Pajakonline.com is one of the business sectors that have been severely affected by the Covid-19 pandemic, considering the core business of the pajakonline.com is to serve tax-related or financial consultations of every problem that there is a taxpayer, as well as the business process itself, is still using conventionally by meeting clients in person, making presentations to each prospective client, collection and processing of data that still use manual means. The ongoing Covid-19 pandemic automatically makes various jobs challenging to do, or if possible to continue to be done, it will be accompanied by various stringent health regulations and protocols. With the design of information technology systems on the web pajakonline.com, related agencies can easily manage their expenditures and revenues based on applicable PPh21 guidelines because the Pajakonline.com web page has contained calculations of tax amount following the status of each employee. Implementing the web Pajakonline.com as one of the fulfilment of the tax automation user experience will significantly help the receipt of tax funds for the country, especially in this pandemic situation. Thus, it can be said that the web Pajakonline.com is ready to operate and run its business into the digital realm